(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper demonstrates on how to design an ambient environment for a group of agents called Swarm exhibiting the Swarm Intelligence. Ambient and Swarm Intelligence areemerging technologies in the field of Artificial Intelligence. The Proposed Ambient Environment aim is to ensure that bad agent should be avoided from collecting the resources. Swarm is a group of homogenous individuals, which interact locally among themselves and their surrounding environment, with no centralized control and from which interesting global behavior emerges. The proposed Swarm is group of agents had to collectively collect the resources from the environment and together has to construct the bridge. The main aim of this research is to check the two parameters- Coordination and Performance. How much coordination to be given so that maximum performance is achieved. Thus concluded that coordination is directly proportional to the performance.